Genomic evidence of population genetic differentiation in deep-sea squat lobster Shinkaia crosnieri (crustacea: Decapoda: Anomura) from Northwestern Pacific hydrothermal vent and cold seep. (February 2020) - Cheng, Jiao; Hui, Min; Li, Yulong; Sha, Zhongli
Abstract: The galatheid squat lobster, Shinkaia crosnieri Baba and Williams, 1998, is one of the few dominant species inhabiting both deep-sea hydrothermal vents and cold seeps. Here, we used mitochondrial cytochrome c oxidase subunit I (mtDNA COI) and nuclear genome-wide single nucleotide polymorphism (SNP) as genetic markers to investigate genetic connectivity of S. crosnieri populations from a hydrothermal vent of Okinawa Through and a cold seep of the South China Sea. MtDNA COI sequence analyses indicated that deep-sea vent population of S. crosnieri was genetically divergent from cold seep population. To obtain deep insights into the evolutionary forces driving this genetic break, we performed restriction-site associated DNA analysis to evaluate the extent of genetic differentiation in S. crosnieri inhabiting both environments on a genome-wide scale, and to assess the role of selective processes in shaping this pattern. Using the assembled survey genome of S. crosnieri as a reference, 12, 963 SNPs were identified for 30 S. crosnieri specimens. The structural and principle component analyses based on SNPs supported genetic differentiation between the vent and seep populations. Evidence for local adaptation of S. crosnieri populations was confirmed by identifying increased population divergence using F ST -based outlier tests, which resulted in 54 potentially locally selected SNPs, indicative of an important role for natural selection as a driver of genetic divergence in this species. Further studies revealed that candidate genes containing outlier SNPs were involved in diverse biological processes, including immunity, transposon and metabolic processes. Overall, our results demonstrated significant genetic divergence between the vent and seep S. crosnieri populations in the Northwestern Pacific and provided clues to understand potential genetic basis underlying local adaptation in S. crosnieri during colonization into deep-sea chemosynthetic ecosystems. Highlights: Clear population structure between Okinawa Trough and South China Sea was revealed in Shinkaia crosnieri . This genetic break is driven by both limited genetic flow and local selective pressures. Adaptive divergence might occur in S. crosnieri inhabiting Iheya North vent and cold seep in the South China Sea.